Effect of ion depth in low energy ion scattering Spectroscopy for evaluating nanostructures - Surachai Pengmanayol (2018)
In order to investigate the nanostructures, the spectroscopy technique providing the information on the top most layers or a few nanometer below the surface is required and the effect of ion depth in low energy ion scattering (LEIS) spectroscopy was investigated by Monte Carlo simulation. Helium ions with the energy of 0.1, 1.0 and 10.0 keV were used as a probe ion in the simulation on the pure element target with atomic number from 3 to 92. The depths which ions can scattering out of the surface and the position just before the scattering of the surface were collected. These are used to indicate the region where the surface information can be gathered in the multiple scattering ions. For 1.0 keV ion, the typical depth for LEIS is only 10 nm from the surface, which is suitable in characterization of nanostructures. The ion penetration depth was also evaluated by collecting the depth of terminated ion inside the target. This indicates the influence of ion into the nanostructure target at this thickness. © 2007 IEEE.